On application of Kalman filters in cohort models - O. I. Ilin (Известия ТИНРО)
On example of walleye pollock at East Kamchatka, one of possible approaches is considered to assess the state of stocks for marine commercial species with usage of the data on age structure in catches. Algorithms for suboptimal filtering and interpolation (extended Kalman smoother and unscented Kalman smoother) are presented for a cohort model of an exploited stock, in presence of uncertainty about true value of the vector of the system parameters.